PROBLEMS OF LAND RESOURCES USE - Afanasiev, O. (Municipal economy of cities. Series: «Economy science», 2024)
The article is devoted to the problems of land protection and rational use. In the study, we analyse the factors leading to degradation and loss of soil fertility. We determined that the negative impact on land is mainly related to the anthropogenic factor. The author points out the role of land as the core national wealth, which, according to the Constitution of Ukraine, is under the special protection of the state. Agricultural lands make up the largest area, but their condition, as well as the condition of other lands, is a matter of concern. We note that the struggle of world powers for economic leadership hinders the environmental problems solution. The article determines that the problems of the use of land resources in Ukraine have only worsened in recent years. Achievements in the agricultural sphere are due to the intensive use and depletion of soils. Intentional and unintentional impact on the earth worsens its condition. The impossibility of adequately calculating the probability of unintended effects on the environment exacerbates the problem. The anthropogenic factor is the main reason for the negative dynamics of the surrounding environment, particularly land resources. Close cooperation of all parties is required to remedy the current situation: land users/land owners, on the one hand, and the state and international organisations, on the other. Scientists and their ideas should be intermediaries between land users/land owners, the state, and international organisations. We propose to strengthen the role of the government in solving problems related to the state of land and their cooperation with international organisations in the fight against desertification and to achieve a zero level of land degradation. We also propose measures to reduce the level of land degradation to reach a neutral level of degradation. At the international level, the ‘United Nations Convention to Combat Desertification in Those Countries Experiencing Serious Drought and/or Desertification, Particularly in Africa’ was adopted. We suggest considering international standards in the effective management of land resources and the experience in forming and implementing land management systems.